Nexus between exports, imports and foreign direct investment: Evidence from Bangladesh - Daror, Hudayfe Osman; Ahmed, Zobayer; Muhumed, Muhumed Mohamed (IIUC Business Review, 2021)
Foreign Direct Investment (FDI) plays a significant role in international trade (IT). Numerous recent studies focused on the FDI-IT nexus and found a strong interrelation between the two variables. The current research empirically examines the causal linkage among imports, exports, and FDI in Bangladesh, utilizing available time-series data from 1980-2015. The study finds that the long-run equilibrium association exists among Exports, Imports and FDI. The study also finds unidirectional causality running from imports and exports to FDI, meaning the rise and fall of exports and imports cause an increase or decrease in FDI of Bangladesh, respectively, and there is no other long-run causality found among other variables. In the short run, unilateral causality is running from imports to FDI, imports to export and exports to FDI. These empirical findings mean that expanding trade can be used to attract more FDI in Bangladesh. Therefore, the study findings strongly support the notion that international trade (exports and imports) stem from the attraction of FDI. IIUC Business Review Vol. 10, Dec. 2021 pp. 25-42